The Gestures in 2–4-Year-Old Children With Autism Spectrum Disorder - Ye, QianYing; Liu, LinRu; Lv, ShaoLi; Cheng, SanMei; Zhu, HuiLin; Xu, YanTing; Zou, XiaoBing; Deng, HongZhu (Frontiers in Psychology, 2021)
Deficits in gestures act as early signs of impairment in social interaction and communication in children with Autism Spectrum Disorder (ASD). This investigation aimed to explore the atypical gesture pattern of ASD children from the dimensions of quantity, communicative function and integration ability, and its relationship with social ability and adaptive behavior. Semi-structured interactive play was used to evaluate gestures of 33 ASD children (24-48 months old) and 24 Typically Developing (TD) children (12-36 months old). The social ability, adaptive behavior and productive language of ASD and TD children were also evaluated by using the Adaptive Behavior Assessment System version II (ABAS- II) and Chinese Communication Development Inventory (CCDI). We found that ASD children produce fewer gestures and have deficits in JA gestures. The deficiency of integrating eye gaze and gesture is the core deficit of ASD children's gesture communication. Relatively, ASD children might be capable to integrate vocalization/verbalization into gestures. SI gestures and the ability to integrate gesture and eye gaze are related to social ability. The quantity of gestures and the ability to integrate gesture with eye gaze are related to adaptive behavior.